2015
DOI: 10.1007/s11103-015-0343-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cuticular wax constituents and genes that contribute to the formation of ‘glossy Newhall’, a spontaneous bud mutant from the wild-type ‘Newhall’ navel orange

Abstract: Navel orange (Citrus sinensis [L.] Osbeck) fruit surfaces contain substantial quantities of cuticular waxes, which have important eco-physiological roles, such as water retention and pathogen defense. The wax constituents of ripe navel orange have been studied in various reports, while the wax changes occurring during fruit development and the molecular mechanism underlying their biosynthesis/export have not been investigated. Recently, we reported a spontaneous bud mutant from the wild-type (WT) 'Newhall' Nav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 68 publications
4
54
0
Order By: Relevance
“…Previous reports have studied the infectious processes and mechanism of Penicillium digitatum for citrus fruits [27][28][29]. Despite the diversity of citrus cuticle composition and architecture being reported [5][6][7][8]10], information about the variations in the chemical composition of citrus fruit cuticle during storage, especially their potential roles in Penicillium digitatum infection, is not available. Similarly, there is a limited understanding of the relative importance and differing roles of waxes and cutin.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have studied the infectious processes and mechanism of Penicillium digitatum for citrus fruits [27][28][29]. Despite the diversity of citrus cuticle composition and architecture being reported [5][6][7][8]10], information about the variations in the chemical composition of citrus fruit cuticle during storage, especially their potential roles in Penicillium digitatum infection, is not available. Similarly, there is a limited understanding of the relative importance and differing roles of waxes and cutin.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that mutations in wax biosynthesis causing glossy surface in Arabidopsis leaf and stem show reduced density of wax crystals and sometimes also alterations in the crystal shape and size (Jenks et al ., 1996). Similar results has been obtained in studies on surfaces of glossy fruits of orange (Liu et al ., 2012; 2015) and cucumber (Wang et al ., 2015a,b). Our study also demonstrated a decrease in the density of epicuticular wax crystal structures in GT fruit compared to WT fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of naturally occurring glaucous lines have identified β-diketones to be responsible for glaucousness in wheat and barley (Hen-Avivi et al ., 2016). Among fruits, orange glossy type mutant fruits showed a decrease in wax load accompanied by reduction in proportion of aldehydes affecting crystalloid formation (Liu et al ., 2012; 2015). In cucumber, CsCER1 -RNAi transgenic lines showing glossy phenotype demonstrated inhibited wax crystallization attributed to decrease in proportion of alkanes as compared to wild type lines (Wang et al ., 2015b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, monounsaturates have been reported as trace components in the waxes of naval orange (Citrus sinensis) fruit (Liu et al, 2015). Alkenes have been reported in the waxes of rice and maize silks (Perera et al, 2010;Qin et al, 2013).…”
mentioning
confidence: 93%